(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
For many – if not most – peace and human rights educators, writing is an indispensable part of being a change agent. As an instrument for reflection, communication, and persuasion, writing is a daily site of encounter between one’s loftiest goals and the particulars of one’s own life. The encounter may take many forms: reports, applications, proposals, scholarly articles and books, blogs, e-mails, websites, social network entries – even the daily “to do” list with its hierarchy of values embedded in the order of jotted items. For educators working within formal settings, there are the additional genres that powerfully define the quality of a learning environment: the syllabus, the written assignment, the power point presentation and lecture notes, the comments on students’ written work. Each in its own way, these forms and genres sustain the inquiry and critical thinking needed to transform violent, unjust social orders into cultures of peace, human rights and dignity.